Evaluating Dose- and Time-Dependent Effects of Vitamin C Treatment on a Parkinson’s Disease Fly Model - Huynh Man Anh; Dao My Linh; Vuu My Dung; Dang Thi Phuong Thao (Parkinson's Disease)
Parkinson’s disease (PD) is a common neurodegenerative disorder and characterized by progressive locomotive defects and loss of dopaminergic neurons (DA neuron). Currently, there is no potent therapy to cure PD, and the medications merely support to control the symptoms. It is difficult to develop an effective treatment, since the PD onset mechanism of PD is still unclear. Oxidative stress is considered as a major cause of neurodegenerative diseases, and there is increasing evidence for the association between PD and oxidative stress. Therefore, antioxidant treatment may be a promising therapy for PD. Drosophila with knockdown of dUCH, a homolog of UCH-L1 which is a PD-related gene, exhibited PD-like phenotypes including progressive locomotive impairments and DA neuron degeneration. Moreover, knockdown of dUCH led to elevated level of ROS. Thus, dUCH knockdown flies can be used as a model for screening of potential antioxidants for treating PD. Previous studies demonstrated that curcumin at 1 mM and vitamin C at 0.5 mM could improve PD-like phenotypes induced by this knockdown. With the purpose of further investigating the efficiency of vitamin C in PD treatment, we used dUCH knockdown Drosophila model to examine the dose- and time-dependent effects of vitamin C on PD-like phenotypes. The results showed that although vitamin C exerted neuroprotective effects, high doses of vitamin C and long-term treatment with this antioxidant also resulted in side effects on physiology. It is suggested that dose-dependent effects of vitamin C should be considered when used for treating PD.